2014
DOI: 10.1038/cmi.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

CD56brightCD25+ NK cells are preferentially recruited to the maternal/fetal interface in early human pregnancy

Abstract: Decidual natural killer (dNK) cells are believed to be critical for maintaining maternal/fetal tolerance and regulating placental vascular remodeling based upon their abundance and unique phenotype during early pregnancy. However, the mechanism for how the dNK cells play such important roles in successful pregnancy remains undefined. Here, we identified a subtype of dNK cells characterized as having a CD3 2 CD56 bright CD25 1 phenotype. We found that CD56 bright CD25 1 NK cells preferentially localize to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 42 publications
(47 reference statements)
0
50
0
1
Order By: Relevance
“…15,36 The environment at the maternal-fetal interface is assumed to modify recruited pNK cells, instructing them to be dNK-like cells in phenotype and function. 28,37 Here, we found that the coculture of pNK cells with trophoblasts significantly increased Th2-type cytokine production and decreased Th1-type cytokine and perforin expression by pNK cells. This makes pNK cells more adaptable to a dNK cell phenotype.…”
Section: Cd16mentioning
confidence: 77%
See 1 more Smart Citation
“…15,36 The environment at the maternal-fetal interface is assumed to modify recruited pNK cells, instructing them to be dNK-like cells in phenotype and function. 28,37 Here, we found that the coculture of pNK cells with trophoblasts significantly increased Th2-type cytokine production and decreased Th1-type cytokine and perforin expression by pNK cells. This makes pNK cells more adaptable to a dNK cell phenotype.…”
Section: Cd16mentioning
confidence: 77%
“…30 These NK cells experience modulation by trophoblasts after enrichment at the maternal-fetal interface. 37 Because Tim-3 was detected on peripheral NK cells and dNK cells in early pregnancy, we speculated here that the Gal-9/Tim-3 pathway may participate in the instruction of pNK cells by trophoblasts. We first determined the expression of Gal-9 in placental trophoblasts.…”
Section: Decidual Tim-3-expressing Nk Cells Display Features Of Immunmentioning
confidence: 83%
“…It was demonstrated that among decidual cells compared to NK cells of peripheral blood many more cells expressed receptor CD25 [33]. At that, more than half of cells present in decidua and expressing CD25 are NK cells, while in peripheral blood, T-lymphocytes make up the majority of CD25 + cells [33]. For NK cells of peripheral blood with CD3 -CD56 bright CD25…”
Section: Cellular and Cytokine Microenvironment Influences Nk Cells Dmentioning
confidence: 99%
“…+ phenotype the reduced expression of inhibiting receptors and increased expression of activation receptors is typical, as well as reduced content of perforin and granzyme B and increased expression of IFNγ and TGF-β [33]. It is supposed that these NK cells can migrate into the uterus and their main function is to secrete cytokines and maintain cytokine microenvironment in the zone of uteroplacental bed at pregnancy [33].…”
Section: Cellular and Cytokine Microenvironment Influences Nk Cells Dmentioning
confidence: 99%
See 1 more Smart Citation